Explaining changes in post-apartheid income and earnings inequality - Hundenborn, Ines Janina (School of Economics, 2021)
This doctoral thesis analyses the changes in income inequality in post-apartheid South Africa. The thesis adds to the existing literature by explaining the underlying causes of the changes in observed income inequality. As such, this thesis applies different decomposition methods to the Gini coefficient. In the analysis of household income sources, traditional static decompositions are supplemented by applying micro-simulations that allow for a dynamic decomposition of changes in income sources reported in household surveys. The results corroborate previous findings of the significant contribution of labour market incomes and governmen grants. However, the application of advanced dynamic methods highlights the effects of changes in other factors, such as investment income and the role of employed household members, which have previously received less attention. Further study of household survey data and a unique set of tax administration data enabled a decomposition of the Gini coefficient of taxable income to investigate the effect of high earners on income inequality and the accuracy of capturing them in household surveys. This analysis highlights a significant weighting issues of high earners in the latest wave of the household survey data. Therefore, when combining the two types of data sets, a significant decrease in overall inequality of taxable income can be found between 2011 and 2014. The results ascertain the vast differences between the top and the bottom of the income distribution and concrete policies addressing both sides of the issue need to be implemented in order to overcome persisting income inequality. Finally, the strong effects of labour market incomes on overall income inequality warrant further investigation. Therefore, changes in earnings inequality are decomposed to assess the effect of changes in the labour market. The application of micro-simulations thereby allows to decompose the changes in earnings inequality into ‘price effect' and ‘endowment effect' but also to assess the effect of changes in labour market participation, employment, occupational structure and unobserved characteristics. The results show that key drivers of an increase in earnings inequality between 1993 and 2012 were changes in the endowments of working age individuals. This effect was partially counteracted by the price effect. The findings show persisting discrepancies between male and female employment in the labour market and the ongoing marginalization particularly of African women which highlights the need for a revision of existing affirmative action laws and their implementation. The National Development Plan offers several strategies for more inclusive growth for South Africa, however, government is already falling behind with its implementation. Therefore, policy makers need to re-examine the efficiency of current social spending and labour laws in order to set the right growth path for the South African economy. The methods utilized throughout this thesis harmonise different sources of information and enable an integrated analysis of the dynamics of the South African income distribution. The static and dynamic decompositions make use of the 1993 household survey of the Project for Statistics on Living Standards and Development (PSLSD) and the 2008 and 2014 National Income Dynamics Study (NIDS). The assessment of high earners is performed by comparing tax administration data provided by the South African Revenue Service (SARS) for the 2010 and 2014 tax years with household survey data from NIDS in 2011 and 2014. Finally, the decomposition of earnings inequality is carried out using data sets from the Post-Apartheid Labour Market Series (PALMS) between 1993 and 2012.